(3bUjOI HGfJ SYGOs - (3GdeGRfj, CHh GdeVqQH, cYH Hf RgjQ Hf CHj Sdei, J(B26(3g`s
(3ChdgG (B:s
(3HGfJ SYGO abdHj Gdjhe eJHhd (B*** (3eJje EKQgG de jaO ecHhds
(3BNQgG (B:s
(3fGbUI GdBNQ, hBNQgG(B: (3dG jaQMhf EPG fGdJ QeGMge (B*** (3bheG hdjShG eLGRjYG EPGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 226s
(3eYLe GdeDdajf(B: 2 / 669s
(3cTa GdXfhf(B: 2 / 1329s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs